IMPLEMENTATION OF DIGITAL MARKETING IN MAINTAINING MSMES DURING THE COVID-19 PANDEMIC - Luckhy Natalia Anastasye Lotte; Oti Kusumaningsih; Norvadewi Norvadewi; Zarkasi Zarkasi; Anggara Setya Saputra (Jurnal Ekonomi, 2022)
According to the Organization for Economic Cooperation and Development, the pandemic has harmed up to 82.9% of MSMEs (OECD). The goal of this study is to find out how digital marketing can help MSMEs survive a pandemic. The data for this study was gathered in three ways: active participatory observation, semi-structured interviews, and document analysis, all using a descriptive qualitative approach with purposive sampling. Source triangulation and technical triangulation were used to validate the data, and interactive model analysis was used to analyze it. According to the study's findings, MSMEs can survive the Covid-19 pandemic by implementing digital marketing in terms of knowledge and its application through participation in seminars, training, and talk shows, as well as knowledge information sharing (knowledge sharing). Digitalization and its application in e-commerce advertising (ads). Innovation, particularly its application in the creation of social media content and the increase of brand awareness.